PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IA UPT SPF SD INPRES MALLENGKERI II MELALUI PENGENALAN KONSEP BUDAYA SETEMPAT MENGGUNAKAN PLATFORM WORDWALL - Andi Rina Purnama Indah; Desi Fitriani; Nurhasfiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to implement the Culturally Responsive Teaching (CRT) approach in the context of character education in class IA at UPT SPF SD Inpres Mallengkeri II. The research was conducted in two learning cycles, each consisting of three meetings, involving 20 students. Qualitative data were collected through observations, interviews, and document analysis to assess student enthusiasm and learning outcomes related to the character values being taught. Data analysis techniques included coding, theme identification, and interpretation of the results from interviews and observations. The findings indicate that the application of CRT, supported by the WordWall platform, successfully increased student enthusiasm in the learning process. In the first cycle, active student participation reached 75%, while in the second cycle, enthusiasm rose to over 90%, accompanied by a significant understanding of character values. These findings underscore the importance of integrating character education into the learning process and the effectiveness of technology in creating a more engaging learning experience. This research is expected to contribute to the development of educational practices that are more responsive to the cultural context of students and enhance their understanding of character values in everyday life.